Hybrid identites Filipino fansubbers of Japanese media and self-construction - Agcaoili, Mizhelle D. (2011)
Along with the increasing accessibility of Japanese media to audiences outside Japan, fansubbing has become a widespread online activity as well. This study focuses on Filipino fansubbers and poses the question, "What hybrid identities do fansubbers construct upon engaging in the activity of fansubbing? The study makes use of Steve Bailey's "hermeneutic subject" in analyzing the responses of five Filipino fansubbers to an interview. The study also employs interpretive textual analysis in examining some of the works of these fansubbers. The conclusion of the study highlights that, within the space of fandom, Filipino fansubbers are hybrid in two ways: (a) they are "prosumers" ho both consume media and produce a new product out of it and (b) they rely on a culturally hybrid identity where they capitalize on an imagined Japanese identity and an internediary English-speaking one.
Keywords: Languages, Mixed; Fans (Persons)